Modeling the Effect of Plants and Peat on Evapotranspiration in Constructed Wetlands - Florent Chazarenc; Simon Naylor; Yves Comeau; Gérard Merlin; Jacques Brisson (International Journal of Chemical Engineering)
Evapotranspiration (ET) in constructed wetlands (CWs) represents a major factor affecting hydrodynamics and treatment performances. The presence of high ET was shown to improve global treatment performances, however ET is affected by a wide range of parameters including plant development and CWs age. Our study aimed at modelling the effect of plants and peat on ET in CWs; since we hypothesized peat could behave like the presence of accumulated organic matter in old CWs. Treatment performances, hydraulic behaviour, and ET rates were measured in eight 1 m2 CWs mesocosm (1 unplanted, 1 unplanted with peat, 2 planted with Phragmites australis, 2 planted with Typha latifolia and 2 planted with Phragmites australis with peat). Two models were built using first order kinetics to simulate COD and TKN removal with ET as an input. The effect of peat was positive on ET and was related to the better growth conditions it offered to macrophytes. Removal efficiency in pilot units with larger ET was higher for TKN. On average, results show for COD a k20 value of 0.88 d-1 and 0.36 d-1 for TKN. We hypothesized that the main effect of ET was to concentrate effluent, thus enhancing degradation rates.